2016
DOI: 10.1096/fj.201500155r
|View full text |Cite
|
Sign up to set email alerts
|

Specialized proresolving lipid mediators in patients with coronary artery disease and their potential for clot remodeling

Abstract: Inflammation in arterial walls leads to coronary artery disease (CAD). Because specialized proresolving lipid mediators (SPMs; lipoxins, resolvins, and protectins) stimulate resolution of inflammation in animal models, we tested whether n-3 fatty acids impact SPM profiles in patients with CAD and promote clot remodeling. Six patients with stable CAD were randomly assigned to either treatment with daily 3.36 g Lovaza for 1 yr or without. Targeted lipid mediator-metabololipidomics showed that both groups had abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 48 publications
4
116
0
3
Order By: Relevance
“…Initial clinical evidence for a relative “resolution deficit” in atherosclerosis was provided by Ho and colleagues, who demonstrated that circulating levels of the SPM aspirin-triggered lipoxin A 4 (ATL; 15-epi-LXA 4 ) were significantly lower in symptomatic peripheral arterial disease patients than in healthy controls, and correlated inversely with clinical severity (Ho, Spite et al 2010). Similar findings have been reported in patients with coronary artery disease as well as cerebrovascular disease (Elajami, Colas et al 2016, Thul, Labat et al 2017). In these settings of advanced atherosclerosis, acute superimposed vascular injury (e.g.…”
Section: Vascular Injury: From Inflammation Through Resolution To Repairsupporting
confidence: 89%
See 2 more Smart Citations
“…Initial clinical evidence for a relative “resolution deficit” in atherosclerosis was provided by Ho and colleagues, who demonstrated that circulating levels of the SPM aspirin-triggered lipoxin A 4 (ATL; 15-epi-LXA 4 ) were significantly lower in symptomatic peripheral arterial disease patients than in healthy controls, and correlated inversely with clinical severity (Ho, Spite et al 2010). Similar findings have been reported in patients with coronary artery disease as well as cerebrovascular disease (Elajami, Colas et al 2016, Thul, Labat et al 2017). In these settings of advanced atherosclerosis, acute superimposed vascular injury (e.g.…”
Section: Vascular Injury: From Inflammation Through Resolution To Repairsupporting
confidence: 89%
“…Evidence for direct effects of SPM on EC and VSMC demonstrates an anti-inflammatory, homeostatic profile of actions that may constitute an important vasculo-protective biochemical pathway (Table 1). SPM are bioactive in the pM-nM range, consistent with levels that have been measured in circulating blood (Colas, Shinohara et al 2014) as well as in a growing range of human biological samples (Brezinski, Nesto et al 1992, Ho, Spite et al 2010, Colas, Shinohara et al 2014, Elajami, Colas et al 2016, Thul, Labat et al 2017). Important for their consideration as candidate vascular therapeutics, we have observed no evidence of toxicity in EC or VSMC even when cells are exposed to micromolar ranges of resolvins and other SPM (Conte MS, unpublished data).…”
Section: Direct Effects Of Spm On Vascular Cellssupporting
confidence: 73%
See 1 more Smart Citation
“…EPA and DHA supplementation for 6 months in post–myocardial infarction patients was associated with a favorable effect on left ventricular remodeling and a significant reduction in noninfarct myocardial fibrosis measured by cardiac magnetic resonance imaging (mean reduction, −5.6%; 95% CI, −10.4% to −0.9%; P =0.022) compared with placebo 35. In a subset of 6 patients from the current study, several resolvins, which have been shown to be present in healthy subjects,36, 37, 38 were absent or present at low levels in CAD patients not on omega‐3 ethyl‐ester; the resolvins were restored or their level increased in those receiving omega‐3 ethyl‐ester 39. The stimulation of resolution of infection and inflammation by resolvins (the downstream products of EPA and DHA) may be responsible for the significantly lower rate of nonserious infectious disease events in the omega‐3 group 40, 41.…”
Section: Discussionmentioning
confidence: 61%
“…More recently, RvD2 was found to prevent thrombosis of the deep dermal vascular network and subsequent dermal necrosis in a mouse burn model 65 . SPM have also been shown to increase macrophage uptake of blood clots in vitro , indicating that SPM may play a role in clot remodeling during resolution 66 . Interestingly, platelet:PMN aggregates formed during self-limited, acute inflammation lead to SPM biosynthesis, which have been shown to reduce human platelet:PMN aggregates 67, 68 .…”
Section: 5 Spms In Thrombosis and Platelet Activationmentioning
confidence: 99%